SISTEM INFORMASI PEMANTAUAN TAHFIDZ AL-QUR’AN BERBASIS WEB DENGAN MENGGUNAKAN METODE EXTREME PROGRAMMING (STUDI KASUS DI RTQ BAIT QUR’ANI TASIKMALAYA) - Aminuddin Muhtarom; Haisyam Maulana; Tuti Rohayati (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
ABSTRACT Rumah Tahfidz Al-Qur'an Bait Qur'ani Tasikmalaya is a non-formal educational institution that focuses on memorizing and reciting the Qur'an. This institution still uses a manual method to report the progress of students' memorization of the Qur'an to their parents. Based on the results of the study, the author tried to design a tahfidz al-Quran reporting system to make it easier for parents to find out their children's achievements in real time which can be accessed from anywhere using a web-based application. The development method used is one of the Agile development methods, namely the Extreme Programming development method. By using the Extreme Programming method, the development of this web-based application can be carried out more flexibly because the Extreme Programming development method involves iterations that are repeated depending on user needs and feedback.